Pengaruh Latihan Mental Terhadap Kepercayaan Diri Pemain Ekstrakurikuler Futsal SMA Negeri 6 Malang - Mario Azriel Iman Chodori; Sapto Adi; Nanang Tri Wahyudi (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2023)
The purpose of this study was to find out whether there was an increase in self-confidence in futsal players after participating in mental training. This study used a pre-experimental research method with 15 futsal extracurricular players at SMA Negeri 6 Malang as subjects. The instrument in this research uses the confidence scale The State Sport Confidence Inventory (SSCI). The data analysis technique used is the paired sample difference test method (paired sample t-test). The results showed that mental training had an effect on increasing the confidence of futsal extracurricular players at SMA Negeri 6 Malang. The test results showed that the mean pre-test result was 79.2, then there was an increase in the post-test, which was 94.6 after mental training. Of the 15 subjects, all experienced an increase. It can be concluded that there is an influence of mental training on the self-confidence of extracurricular players at SMA 6 Malang.